Modal testing of masonry constructions by ground-based radar interferometry for structural health monitoring: A mini review - Camassa, Domenico; Vaiana, Nicolò; Castellano, Anna (Frontiers in Built Environment, 2023)
Modal testing is one of the most effective experimental techniques for the Structural Health Monitoring (SHM) of masonry constructions, as it provides useful information for the calibration of structural models and for the assessment of structural damage. However, the application of modal testing to masonry constructions is sometimes hindered by the complexity of the conventional experimental set-up, which is generally based on contact sensors. In order to overcome this issue, several researchers are exploring the application of the ground-based radar interferometry, which is an increasingly popular measurement technique for remotely monitoring displacement and vibration of structures. Given the recently increasing number of articles on this subject, here we propose a mini review on the most significant works dealing with the application of ground-based radar interferometry for modal testing of masonry constructions. In particular, we show the current state of the art and highlight the main research gaps with the purpose of assessing the effectiveness of ground-based radar interferometry for the structural health monitoring of these constructions. Our mini review is primarily aimed at engineers and scientists who already know about modal testing and radar interferometry technique and are interested in the specific application to masonry constructions.